2017
DOI: 10.1186/s13063-017-1859-x
|View full text |Cite
|
Sign up to set email alerts
|

Methods of defining the non-inferiority margin in randomized, double-blind controlled trials: a systematic review

Abstract: BackgroundThere is no consensus on the preferred method for defining the non-inferiority margin in non-inferiority trials, and previous studies showed that the rationale for its choice is often not reported. This study investigated how the non-inferiority margin is defined in the published literature, and whether its reporting has changed over time.MethodsA systematic PubMed search was conducted for all published randomized, double-blind, non-inferiority trials from January 1, 1966, to February 6, 2015. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 20 publications
2
63
0
Order By: Relevance
“…This margin was used in the ROCKET AF trial, which was defined based on the limit of the 95% CI of the risk ratio of warfarin vs placebo in the reduction of stroke, or systemic embolism that was pooled from six placebo-controlled trials in patients with AF (ie, noninferiority was analyzed using the fixed-margin method). 18,33,34 To assess the primary outcome, a minimum of 2300 patients in each group will provide a power of at least 80% to demonstraste noninferiority of rivaroxaban to warfarin. These calculations were based on the noninferiority margin HR 1.46, one-sided significance level of 0.025, a mean follow-up time of 2 years, and an event rate of the primary outcome of 2.3% per patient-years in both study groups with an anticipated HR of 1.…”
Section: Discussionmentioning
confidence: 99%
“…This margin was used in the ROCKET AF trial, which was defined based on the limit of the 95% CI of the risk ratio of warfarin vs placebo in the reduction of stroke, or systemic embolism that was pooled from six placebo-controlled trials in patients with AF (ie, noninferiority was analyzed using the fixed-margin method). 18,33,34 To assess the primary outcome, a minimum of 2300 patients in each group will provide a power of at least 80% to demonstraste noninferiority of rivaroxaban to warfarin. These calculations were based on the noninferiority margin HR 1.46, one-sided significance level of 0.025, a mean follow-up time of 2 years, and an event rate of the primary outcome of 2.3% per patient-years in both study groups with an anticipated HR of 1.…”
Section: Discussionmentioning
confidence: 99%
“…Although the NI question can be relevant in the phase II setting, 5 it is not usually considered on designing single-arm clinical trials in early clinical development. 30,31 Previous forays into precision medicine have shown that correctly identifying the target population and associated predictive biomarkers may be more critical for treatment success than simple demonstration of superior e cacy against an alternative. 22,23 Consequently, designing a proof-of-concept phase II study that permits NI analysis, if the superiority criteria cannot be met, will allow for more informed decisions that consider e cacy and other parameters, such as safety, cost, and biomarker strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot investigation of our patients, the mean (± standard deviation) of the cumulative 24h opioid (sufentanil) consumption after laparoscopic nephroureterectomy was about 25.7 (±2.0) μg with TPVB, and 35 (±14.0) μg with non-block respectively. The non-inferiority margin was set as 5 (unit: μg; clinical practice treated it as an acceptable difference) [27]. With a signi cance level of α=0.05 and a power of 1-β= 90%, the sample size required to detect difference was 77 patients in each group.…”
Section: Sample Size Calculationmentioning
confidence: 99%